Penerapan Market Basket Analysis Dengan Metode Apriori Pada WFZ Book Store - Wahyuni Fithratul Zalmi (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2023)
WFZ Book Store is a Book Store that provides various types of books. The sales process is done offline where the costumer has to visit the store to make a purchase. The process of recording data using the ledger makes it difficult for WFZ Book Store to make sales reports because it has to collect transaction data in the ledger, it causes difficulties to know the available Book stock because it has to check every sales transaction in the ledger. WFZ Book Store requires an information system that can manage book sales data onlineagarcostumers can easily view book data, stockand book online reservations. With the wfz Book Store information system can facilitate the customer in managing book data and store customer data that has made transactions also WFZ Book Store does not find it difficult to provide book purchase transaction data for the customer, so that the data can be used for book recommendations by finding the set of data that most often appear in a data set. Datamining techniques have been widely used to overcome existing problems, one of which is the application of a-priori algorithms to find association rules formed from book purchase transaction datasets. So it will be known the association between the title of the book purchased. The association rules between book titles formed from the mining process can later be used by the WFZ Book Store to increase the number of books purchased, besides that it can be used for the procurement of books from the association rules of frequently purchased books, it can also be developed into a knowledge base for the book purchase recommendation system. The Output is in the form of a priori algorithm analysis software.